Friends or foes? Novel antimicrobials tackling MDR/XDR Gram-negative bacteria: a systematic review - Dan, Mihai Octavian; Tǎlǎpan, Daniela (Frontiers in Microbiology, 2024)
Gram-negative bacteria have been one of the most studied classes in the field of microbiology, especially 3 in the context of globally alarming antimicrobial resistance levels to these pathogens over the course of the 4 past decades. With high numbers of these microorganisms being described as multidrug-resistant (MDR), 5 or even extended-drug-resistant (XDR) bacteria, specialists in the field have been struggling to keep up 6 with higher prevalence of difficult-to-treat infections caused by such superbugs. The FDA approval of novel 7 antimicrobials, such as cefiderocol (FDC), ceftolozane/tazobactam (C/T), ceftazidime/avibactam (CZA), 8 imipenem/relebactam (IMR), sulbactam/durlobactam (SUL-DUR) and phase 3 clinical trials' results of 9 aztreonam/avibactam (ATM-AVI) has proven that, while all these substances provide encouraging efficacy 10 rates, antibiotic resistance keeps up with the pace of drug development. Microorganisms have developed 11 more extensive mechanisms of resistance in order to target the threat posed by these novel antimicrobials, 12 thus requiring researchers to be on a constant lookout for other potential drug candidates and molecule 13 development. However, these strategies require a proper understanding of bacterial resistance mechanisms 14 to gain a comprehensive outlook on the issue. The present review aims to highlight these six antibiotic 15 agents, which have brought hope to clinicians during the past decade, discussing general properties of these 16 substances, as well as mechanisms and patterns of resistance, while also providing a short overview on 17 further directions in the field.